2013
DOI: 10.1016/j.aju.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The use of an acellular collagen matrix in penile augmentation: A pilot study in Saudi Arabia

Abstract: ObjectivesTo assess the use of an acellular collagen matrix (Pelvicol, Bard Medical, Covington, GA, USA), a successful agent for reconstructive surgery, for enhancing penile girth.Patients and methodsBetween June and December 2011, 18 patients (mean age 24 years, range 19–38) had their penis augmented with Pelvicol; the mean (range) penile circumference was 9.2 (7–13) cm before treatment. They were divided into two groups; the first (10 patients) had a Pelvicol sheet of 8 × 12 cm inserted through a V–Y suprapu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“… 82 A pilot study assessing an acellular collagen matrix reported results varying by ADM insertion method, with a bilayer inserted through V-Y suprapubic incision producing greater circumference increases and patient satisfaction. 83 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 82 A pilot study assessing an acellular collagen matrix reported results varying by ADM insertion method, with a bilayer inserted through V-Y suprapubic incision producing greater circumference increases and patient satisfaction. 83 …”
Section: Resultsmentioning
confidence: 99%
“…One study reported that 60.3% of patients experienced erectile discomfort and 12.8% had no obvious augmentation effects when treated with ADM. 82 Reported complications include severe penile oedema, ischemic shaft ulcers, hematomas and wound infections. 82 , 83 Upon suturing the ADM to Buck’s fascia, micro-branches of the dorsal nerve of the penis may become covered and lead to less receptor threshold. 84 Additionally, a thick ADM may affect proprioception receptors in the deep tissue and on the skin surface, leading to abnormal temperature and pressure differences.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ADM has been used with increased frequency over the last decade to assist during prosthetic breast reconstruction and other reconstructive surgeries. [ 20 22 ] ADM was also used for patients with penile augmentation and no major complications occurred in the patients received penile augmentation with ADM. [ 4 , 5 , 7 ] Alei et al used porcine dermal acellular grafts for penile augmentation in 69 candidates and followed for more than 1 year. They reported a 40% increase in penile girth during flaccidity, and 22% during erection with no major complications.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] With this approach, through a short dorsal incision at the base of the penis, the scar is concealed in a crease covered by pubic hair and thus hardly visible. Although a survey conducted by Tealab et al showed that penile augmentation by porcine acellular dermal grafts might negatively affect male sexual status (4 in 18 patients reported decreased penile sensation at 6-month visit), [ 5 ] penile enlargement by implantation of ADM was a safe and effective operation in most of the reports [ 4 , 6 ] and, no major complications occurred in the patients received penile augmentation by ADM. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%